Bupropion Induced Hyponatremia in an Elderly Patient: A Case Report and Review of the Literature - Sahil Munjal; Yvette Smolin (Case Reports in Psychiatry)
We present the case of a 72-year-old female with a major depressive episode who developed hyponatremia associated with bupropion. In reviewing the literature, there are only a few case reports which pertain to this topic. The clinical symptoms of hyponatremia can be misinterpreted as a worsening of the primary psychiatric illness and can lead to potentially serious consequences if not fully evaluated. We recommend that clinicians should be well aware of this side effect and that sodium levels should be checked within the first 2 weeks after initiating treatment in patients, especially those with additional risk factors for hyponatremia, such as older age, female sex, diuretic use, low BMI, and unexplained mental status changes at any time during treatment with antidepressants. The risk for hyponatremia associated with mirtazapine appears to be low and its use can be helpful in patients who have developed hyponatremia induced by other antidepressants and who experienced symptoms of weight loss and insomnia.